Complete Characterization of Weak-Homodyne Photon-Number-Resolving Detectors: Applications to Non-Classical Photonic State Reconstructions - Coldenstrodt-Ronge, H; Puentes, G; Cohen, O; Noriega, F; Yang, X; Lundeen, J; Smith, B; Walmsley, I; IEEE (2010)
A novel detector combining phase sensitivity and photon-number resolution is experimentally characterized by measuring its positive-operator-value measurement set. Direct application to tomographic reconstruction of heralded single-photon states is presented. ©2010 Optical Society of America.